2018
DOI: 10.1111/jop.12698
|View full text |Cite
|
Sign up to set email alerts
|

Density and location of CD3+ and CD8+ tumor‐infiltrating lymphocytes correlate with prognosis of oral squamous cell carcinoma

Abstract: Background Tumor‐infiltrating lymphocytes (TILs) are regarded as adaptive immune response of the host to cancer cells and valuable prognostic factors. Here, we sought to characterize the densities and locations of CD3+ and CD8+ TILs in primary oral squamous cell carcinoma (OSCC) samples and assess their clinicopathological and prognostic significance. Methods A total number of 169 OSCC samples from 2 independent patient cohorts (Nanjing cohort, 93 cases; Wuxi cohort, 76 cases) were retrospectively collected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 30 publications
4
61
0
Order By: Relevance
“…Mounting evidence has established that deregulated immune of host and excessive systemic or local inflammation facilitates tumor overgrowth, metastatic spreading, and therapeutic resistance (Diakos, Charles, McMillan, & Clarke, ; Shalapour & Karin, ). Previous reports have revealed that the presence and functional status of tumor‐infiltrating lymphocytes usually significantly associate with tumor onset and progression as well as clinical response to immunotherapy (Bindea, Mlecnik, Angell, & Galon, ; Zhou et al, ). Measurements of tumor‐infiltrating neutrophils, lymphocytes, and macrophages have indicated their prognostic values in a broad spectrum of human cancers (Galon et al, ; Nguyen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has established that deregulated immune of host and excessive systemic or local inflammation facilitates tumor overgrowth, metastatic spreading, and therapeutic resistance (Diakos, Charles, McMillan, & Clarke, ; Shalapour & Karin, ). Previous reports have revealed that the presence and functional status of tumor‐infiltrating lymphocytes usually significantly associate with tumor onset and progression as well as clinical response to immunotherapy (Bindea, Mlecnik, Angell, & Galon, ; Zhou et al, ). Measurements of tumor‐infiltrating neutrophils, lymphocytes, and macrophages have indicated their prognostic values in a broad spectrum of human cancers (Galon et al, ; Nguyen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, intratumoral infiltration by diverse types of lymphocytes (tumor‐infiltrating lymphocytes, TILs) has been associated with favorable or inferior prognoses in several human cancers including OSCC . We have recently reported that high densities of CD3 + and CD8 + TILs at tumor invasive margins (IM) as well as CD45RO + at tumor center (CT) in OSCC were significantly associated with increased overall and disease‐specific survival and served as independent prognostic factors for patient survival . However, given the complex immune contexture in human tumors, assessment of individual types of TIIs might have prognostic prediction with moderate accuracy .…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[10][11][12][13] We have recently reported that high densities of CD3 + and CD8 + TILs at tumor invasive margins (IM) as well as CD45RO + at tumor center (CT) in OSCC were significantly associated with increased overall and disease-specific survival and served as independent prognostic factors for patient survival. 14,15 However, given the complex immune contexture in human tumors, assessment of individual types of TIIs might have prognostic prediction with moderate accuracy. 16 Integrating multiple immune features into a single model would substantially improve the prognostic value and power over that of single biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…The increased tumor growth of MC38‐Sia null cells could be attributed to reduced CD8 + T cell frequencies present within the tumor. Reduced migration of CD8 + T cells toward the tumor core has been correlated with bad prognosis . As we did not address the localization of the T cells within the tumor microenvironment, we cannot rule out that CD8 + T cells were hampered in reaching the tumor core.…”
Section: Discussionmentioning
confidence: 95%